2000
DOI: 10.1002/1520-6793(200012)17:12<1059::aid-mar3>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

I'll have what she's having: Gauging the impact of product placements on viewers

Abstract: Product placement in TV shows is becoming increasingly common, yet little is known about its effectiveness nor even how to define and measure such effectiveness. This research examined the effectiveness of product placement with the use of two different types of measures: explicit measures that tap memory directly (with the use of a recognition and recall task), and an implicit measure that measures the effect of exposure on product choice indirectly. It was hypothesized that the ability of product placement t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
185
0
19

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(215 citation statements)
references
References 22 publications
(33 reference statements)
6
185
0
19
Order By: Relevance
“…The characteristic of product placement can be differentiated into three dimensions, modality, prominence, and plot connection. Modality is the presence of the brand in the form of visual or auditory (Law & Braun, 2000;Russell, 2002). The level of visual placement can be varying based on the size, duration, centrality, position, f r e q u e n c y , a n d ot h e r s , l i k e w i s e , t h e l e v e l o f a u d i t o ry pl a c e m e n t , f r e q ue n cy , emphasizing, and others.…”
Section: Placement Prominencementioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic of product placement can be differentiated into three dimensions, modality, prominence, and plot connection. Modality is the presence of the brand in the form of visual or auditory (Law & Braun, 2000;Russell, 2002). The level of visual placement can be varying based on the size, duration, centrality, position, f r e q u e n c y , a n d ot h e r s , l i k e w i s e , t h e l e v e l o f a u d i t o ry pl a c e m e n t , f r e q ue n cy , emphasizing, and others.…”
Section: Placement Prominencementioning
confidence: 99%
“…On the other hand, subtle placements are mentioned or showed less prominently, smaller size, shorter time exposure, placed as background and others (Gupta & Lord, 1998;Cowley & Barron, 2008;Dens et al, 2012). By the nature of its appearance, numbers of studies have found that prominent placement is more likely to be recognized than subtle placement (Law & Braun, 2000;Lehu & Bressoud, 2008;Dens et al, 2012;Gillespie et al, 2012) and more likely to attract viewers' attention (Gupta & Lord, 1998).…”
Section: Placement Prominencementioning
confidence: 99%
“…A proeminência pode ser operacionalizada pelo tamanho do produto ou logotipo, pelo grau de centralização na tela, pela sua integração ou centralidade na estória do programa televisivo, pelo número de menções, pelo tempo de duração na tela, pela sua força, pela modalidade, dentre outros (Babin & Carder, 1996;Bhatnagar et al, 2004;Gupta & Lord, 1998;Law & Braun, 2000;Russell, 2002).…”
Section: Dimensões Do Placementunclassified
“…Além disso, já existem trabalhos sobre a memória no que se refere ao placement. Por exemplo, estudos encontraram que a proeminência de um placement tem um impacto positivo sobre a lembrança da marca anunciada do que um placement sutil (Babin & Carder, 1996;Brennan et al, 1999;D'Astous & Chartier, 2000;Gupta & Lord, 1998;Law & Braun, 2000). Isso porque, segundo , há um processamento mais intenso do placement proeminente do que de um placement sutil, aumentando, consequentemente, a memorização pelo consumidor.…”
Section: Memóriaunclassified
See 1 more Smart Citation